Web Development and Assistance in Pancuran Gading Village, Kampar Regency: Pengembangan Dan Pendampingan Web Desa Pancuran Gading Kabupaten Kampar - Guntoro Guntoro; Jeni Wardi; Anto Ariyanto; Widya Apriani; Lisnawita Lisnawita; Olivia Anggie Johar (CONSEN: Indonesian Journal of Community Services and Engagement, 2022)
Pancuran Gading Village is one of the villages in the Tapung sub-district, Kampar Regency, Riau province. Therefore, it is necessary to develop and assist the Pancuran Gading Village website, Kampar Regency. Currently Pancuran Gading Village will be used as a pilot village by the Ministry of Villages. Therefore it is necessary to improve existing facilities and one of the pilot villages is a digital village. The problem faced by partners is that there is no village website yet. The village website is a media of information for residents or society in general. The methods for implementing this service are preparation and planning, field surveys and interviews, data collection, website design and development, implementation of mentoring and website handover, evaluation and final reporting. The result of this service is in the form of a web profile for Pancuran Gading Village. And then provide assistance regarding the use of the website..